Optimization of wavy geometries for enhanced condensation heat transfer on vertical plates: An experimental study - Omid Karimi; N.M. Nouri (Case Studies in Thermal Engineering, 2024)
In this study, macro-scale wavy geometries are used to enhance condensation heat transfer on vertical plates. Three wavy plates with different amplitudes (3.33 mm, 4.17 mm, and 5.56 mm) were compared to a flat plate over a temperature difference range of 12K–50K. For each plate configuration, heat transfer coefficient (HTC), enhancement factor (EF), heat flux (q), and Reynolds number (Re) were measured. Several studies have demonstrated that wavy surfaces offer better performance than flat surfaces, with the highest performance showing up for the 4.17 mm amplitude plate (Wave-2). At higher temperature differences, this optimal configuration achieved enhancement factors up to 1.31. As a result of the study, Reynolds numbers for the largest amplitude plate were 2.4 times higher than for the flat plate, indicating that increasing wave amplitude does not necessarily result in better heat transfer. These findings provide valuable insights for optimizing heat exchanger design in various industrial applications, offering a practical and cost-effective approach to improving falling film condensation heat transfer efficiency.